2012
DOI: 10.1183/09031936.00199911
|View full text |Cite
|
Sign up to set email alerts
|

Dose response of continuous positive airway pressure on nasal symptoms, obstruction and inflammationin vivoandin vitro

Abstract: Obstructive sleep apnoea is a common condition associated with cardiovascular risk. Continuous positive airway pressure (CPAP) is an effective treatment but is associated with nasal side-effects, which hinder compliance and may result from inflammation.We investigated whether CPAP was pro-inflammatory to human subjects in vivo, and to cultured bronchial epithelial cells in vitro. In vivo, we further investigated whether induction of nasal inflammation was associated with the development of systemic inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…These results supported previous research that reports a high prevalence of nasal symptoms after non-humidified CPAP. 45 In contrast, humidified CPAP was associated with less prevalence of nasal symptoms, which suggests that dryness of CPAP pressure increases the acute nasal symptoms after a period of 30 min. The discomfort score was partially increased with the non-humidified CPAP, and this finding was likely to be related to the high prevalence of nasal symptoms that was reported under the same condition.…”
Section: Discussionmentioning
confidence: 97%
“…These results supported previous research that reports a high prevalence of nasal symptoms after non-humidified CPAP. 45 In contrast, humidified CPAP was associated with less prevalence of nasal symptoms, which suggests that dryness of CPAP pressure increases the acute nasal symptoms after a period of 30 min. The discomfort score was partially increased with the non-humidified CPAP, and this finding was likely to be related to the high prevalence of nasal symptoms that was reported under the same condition.…”
Section: Discussionmentioning
confidence: 97%
“…Impairment of NMC can result in diseases of the upper airways like chronic rhinosinusitis . Several studies demonstrated that NMC is affected by using CPAP …”
Section: Pressure‐related Side Effectsmentioning
confidence: 99%
“…inflammation) in a variety of cells and tissues . For example, some clinical and experimental studies have reported on local and systemic inflammatory responses with n‐CPAP . It has been specifically shown that n‐CPAP application can cause inflammation due to the mechanical stimulus on the nasal mucosa .…”
Section: Pressure‐related Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the gold standard for management of clinically significant obstructive sleep apnea patients [1]. However, it has been reported to be associated with a high prevalence of local nasopharyngeal side effects such as increased neutrophil in the nasal mucosa [2,3], and it may induce upper airway inflammation [4]. It has been suggested that airway drying or direct distension of nasal mucosa are responsible of the nasopharyngeal inflammation.…”
Section: Introductionmentioning
confidence: 99%